Pengaruh Perencanaan Anggaran, Pelaksanaan Anggaran, Revisi Anggaran, Kompetensi SDM, dan Pengadaan Barang dan Jasa terhadap Penyerapan Anggaran - Christofer, Jody; Darmawati, Deni (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
One important indicator to assess the performance of the State Budget is by measuring the level of budget absorption in budget implementation. The amount of budget alocation that can be reaized can reflect the functioning of the government such as driving economic growth, more even distribution, and maintaining economic stability. Given the importance of budget absorption in driving the nation's economy, it is necessary to conduct testing and anaysis of factors that can affect budget absorption. This study aims to anayze the influence of budget planning, budget implementation, budget revision, human resource competency, and procurement of goods and services on budget absorption. The study uses purposive sampling method as the research method and employs multiple regression anaysis model. The results show that budget revision has an influence on budget absorption. Meanwhile, budget planning, budget implementation, human resource competency, and procurement of goods and services do not have an influence on budget absorption.